The Impact of European Integration on Adjustment Pattern of Regional Wages in Transition Countries: Testing Competitive Economic Geography Models - Joze P. Damijan; Crt Kostevc (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
In the present paper, we augment the Fujita-Krugman-Venables (FKV) economic geography model by breaking the implied regional symmetry and by introducing a second factor of production, capital, in order to study the within-country regional effects of trade liberalization. In contrast to the Krugman (1991) model, the FKV and our model do not predict typical core ?periphery regional polarization as labor is assumed to be either imperfectly mobile and/or capital is perfectly mobile between regions. Both models result in a non-monotonic, U-shaped response of relative regional wages to trade liberalization. Major difference between the two approaches is that our model allows for FDI flows between countries. FDI inflows are shown to accelerate the regional adjustment process in the home country, as they are initially attracted to poor, border regions characterized by lower wages and higher returns to capital. Our model therefore results in a faster convergence of relative regional wages, i.e. in a more upward and to the right shifted U-shaped response of relative wages. In addition, we then examine the exact adjustment pattern of relative regional wages in five transition countries after they have liberalized their trade with the EU. We study which of the three competitive EG models is a more appropriate approximation of the actual regional adjustment pattern in selected transition countries.
Keywords: 330; Regionale Lohnstruktur; Europäische Integration; Wirtschaftsgeographie; Außenhandelsliberalisierung; Osteuropa